Effect of Low Cost Iron Oxide with Si Additive on Structural Properties of Ni-Zn Ferrite: Iron Oxide Effect on Ni-Zn Ferrite - Ghazanfar, Uzma (Biological Sciences - PJSIR, 2010)
Mixed Ni-Zn ferrites (x = 0.66, 0.77, 0.88, 0.99) were prepared by double sintering ceramic method using locally available low cost Fe2O3 with 0.5% (by wt) of Si additive. The chemical phase analysis, carried out by X-ray powder diffraction method, confirms the major phase of Ni-Zn ferrite. Study of the effect of composi- tion on structural properties of ferrite system revealed a decreasing trend of lattice parameters with increasing Ni content. X-ray density and mass density increase with increasing Ni content, which in turn decreases the poros- ity due to successive presence of Si in Fe2O3. This decrease in porosity along with chemical homogeneities, distribution of phases and grain formation were also observed in scanning electron micrographs.